Land suitability in sustainable cultivation practices for porang (Amorphophallus oncophyllus L.) in Pasuruan Regency, Indonesia - Sarah Nabila Fitriyanti; Purwadi; Moch. Arifin (Universitas Lancang Kuning, 2023)
Porang (Amorphophallus oncophyllus L.) stands as a prominent agricultural product in Indonesia. As the demand for porang continues to grow, it becomes crucial to balance it with the expansion of suitable land for cultivation. The selection of appropriate land for crop planting requires a thorough analysis of land feasibility, commonly known as land suitability assessment. This study aims to evaluate land feasibility, identify limiting factors, and explore potential solutions for sustainable cultivation of porang in Sumberejo Village, Pasuruan, East Java. The research was employed by a matching method for land suitability assessment based on climatic, physical, and chemical data. The development of a land suitability map was achieved through the overlay of various stages using land characteristic information. The findings reveal that the residents' lands fall within the actual land classes of S3 (suitable marginal) and N (not suitable), with base saturation (nr3) and slope (eh) identified as the primary limiting factors. To improve the suitability of the selected lands, several recommendations were proposed, including the implementation of cover crops, terracing practices, and the addition of potassium-rich organic matter derived from bamboo waste. These recommendations have the potential to elevate the land class to S2 (suitable) and S3 (suitable marginal), thereby addressing the identified limitations and promoting sustainable porang cultivation.